2005
DOI: 10.1007/s10681-005-1691-3
|View full text |Cite
|
Sign up to set email alerts
|

The nabicol: A horticultural crop in northwestern Spain

Abstract: Nabicol (B. napus L. var. pabularia) is a traditional crop in the Northwest of Iberian Peninsula (South of Galicia and North of Portugal) where it is grown during the winter season on small farms and gardens using traditional varieties. A collection of 36 populations of nabicol from Galicia (northwestern Spain) was evaluated during 2002 and 2003 in two locations and two growing seasons (spring/summer and autumn/spring) for 28 agronomic and morphological traits. The objectives of this study were to: (i) evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 16 publications
1
26
0
2
Order By: Relevance
“…a distância proposta por Gower foi também utilizada por Rodríguez et al (2005) Foi possível observar, também, a presença de sintomas característicos da bacteriose, causada por Xanthomonas campestris pv. Passiflorae, e verrugose, causada por Cladosporium cladosporioides em genótipos avaliados, exceto para P. gibertii, P. mucronata (Grupo i) e P. morifolia (grupo ii).…”
Section: Resultsunclassified
“…a distância proposta por Gower foi também utilizada por Rodríguez et al (2005) Foi possível observar, também, a presença de sintomas característicos da bacteriose, causada por Xanthomonas campestris pv. Passiflorae, e verrugose, causada por Cladosporium cladosporioides em genótipos avaliados, exceto para P. gibertii, P. mucronata (Grupo i) e P. morifolia (grupo ii).…”
Section: Resultsunclassified
“…acephala) and nabicol (B. napus var. pabularia) (Rodriguez et al, 2005;Picoaga et al, 2003) have shown that the morphological characteristics (glossy leaves) are connected to resistance toward lepidopterous species. In the case of generalist insects, e.g.…”
Section: Includementioning
confidence: 99%
“…Jointly analyzing quantitative and qualitative variables can provide a better indication of existing variability (ROCHA et al, 2010). Gower's distance (1971) is a lowcomplexity joint analysis procedure which has been used in several characterization and evaluation studies of germplasms (BERTAN et al, 2009;GONÇALVES et al, 2008;MOURA et al, 2010;QUINTAL et al, 2012;ROCHA et al, 2010;RODRÍGUEZ et al, 2005;TSIVELIKAS et al, 2009;VIEIRA et al, 2007). Therefore, in this study, we conducted joint analysis to characterize and evaluate the genotypic divergence of 14 accessions of Cucurbita moschata collected in the northern region of the State of Rio de Janeiro using qualitative and quantitative variables.…”
Section: Introductionmentioning
confidence: 99%